Effects of irrigation and fertilization on soil salt migration, yield, and water use efficiency of winter wheat in the Yellow River Delta. Issue 4 (16th June 2022) - Chen, Huanyu; Ren, Angyan; Hu, Zhaohua; Jia, Chunqing; Wang, Jianlin
Abstract: Irrigation and fertilization are the most effective measures to inhibit soil salt accumulation and increase yield of wheat ( Triticum aestivum L.) grown in saline soils. The present study used a split‐plot experimental design with irrigation as the main plot and fertilizer application as the subplot from 2014 to 2016. The experiment had four levels each of irrigation (W0, no irrigation; W1, one irrigation; W2, two irrigations; W3, three irrigations) and fertilization (M, no fertilizer; Y, cow manure; W, chemical fertilizer; and H, 50% cow manure and 50% chemical fertilizer). The study identified sowing, jointing, and maturity as the major salt accumulation periods. After irrigation, the 0‐ to 20‐cm soil salinity during presowing, jointing, and grain filling decreased by 1.09, 0.28, 0.19 g kg −1, and 0.76, 0.46, and 0.23 g kg −1, from 2014 to 2016. The wheat roots were mainly distributed in the 0‐ to 30‐cm soil layer. Meanwhile, wheat evapotranspiration (ET) ranged from 153 to 402 and 202 to 451 mm from 2014 to 2016, respectively; and the ET under W3W were 2.62‐ and 2.23‐times higher than W0M. Additionally, W3W increased yield of wheat by 567.0 and 422.2% from 2014 to 2016, compared with W0M. Generally, the water use efficiency (WUE) decreases as irrigation increases; however, this study found no significant difference in WUE between W2 and W3. Meanwhile, the chemical fertilizer resulted in the highest WUE, 3.16‐ and 2.63‐times higher than no fertilizer. Thus, the study proposes W3W as a suitable treatment for wheat in the Yellow River Delta. Core Ideas: Irrigation in combination with chemical fertilizer application reduced soil salinity by improving salt leaching. The wheat roots were mainly distributed in the 0‐ to 30‐cm soil layer, with 97% within 0 to 20 cm. The increase in the number of irrigations reduced the water use efficiency (WUE) and chemical fertilizer enhanced WUE. Three irrigations and chemical fertilizer application significantly elevated wheat evapotranspiration and yield.